Ukrainian as a foreign language in the aspect of linguo-didactic testing - СамусенкоO.; Шевченко, М. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The article is devoted to problems of building a uniform testing system for Ukrainian as a foreign language according to the educational standards. The current problem, on the one hand, is connected with the need for providing conditions for social and prognostic, academic and organizational, legal, personnel, material and financial, technical conditions necessary for creation of a test center and, on the other hand, has to do with scientific and theoretical (lingo-didactical) rationale of the testing system and development of mechanisms of its implementation in practice. The article presents the ways of development, standardization and approbation of Ukrainian language certification tests. An attempt was made to characterize modern ways of researching testing methods and for assessment of students; to analyze the all-European recommendations on language education in regards to testing; to illustrate problems of development and implementation of certification tests of Ukrainian as a foreign language. Scientific and methodic manuals in teaching languages as foreign ones and testology were used as the study material. The language testing was chosen as a study object; national and international achievements in language testing and expedience of their usage in teaching Ukrainian as foreign language were used as the subject of analysis. The authors conclude that the unified system of recognizing the proficiency level of Ukrainian as a foreign language should be built with consideration of its usage purpose, skills and abilities in using the language means for implementing certain tactics of verbal behavior in the main areas of verbal activity, and thus the certification tests should contain reading, speaking, listening and writing assignments in accordance with respective requirements. The vocabulary and grammar material can be examined additionally using tests according to the program extent of a proper level. The unified programs and certification tests will allow considering the requirements that follow from the purpose of assuring a certain level of the Ukrainian language proficiency, can increase the learning efficiency and identify the learning process, whereas the academic and methodic work conducted in parallel with the learning process will allow the lingo-didactic professionals to evaluate the materials immediately.